The effects of seed damage on crop production - Chin, Hoong Fong (Incorporated Society of Planters, 1975)
Seeds of soybean (Glycine max L.) c.v. Ogden and French bean (Phascolus vulgaris L.) c.v, Brown Beauty with cotyledonary damage produce small weak seedlings on germination. With freshly harvested damaged seeds the percentage germination is not affected under experimental conditions. In term of vegetative growth, the di1Terence in dry matter production and leaf area are obvious and significant in the seedling stage. At maturity these differences are not apparent as long as 50 per cent of the cotyledonary tissues are undamaged. However, plants from damaged seeds are delayed in their maturity, resulting in an uneven crop. At harvest the yield from badly damaged seeds can be lowered by 35 and 21 per cent for mechanically damaged soybean seeds and weevil-damaged French bean seeds respectively.